Analysis of the Conformity Level of an Assessment in the Functional Movement Screen Test - Kałużna, Anna; Kałużny, Krystian; Wołowiec, Łukasz; Cichosz, Michał; Zukow, Walery; Kochański, Bartosz; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Introduction. The Functional Movement Screen (FMS) is a concept created by Gray Cook and Lee Burton for a comprehensive functional evaluation. FMS allows for the assessment of the risk of injury, the assessment of functional mobility, stability and neuromuscular coordination, and the definition of limitation and asymmetry within the locomotive system. Aim of the study. The aim of the study is to analyze the consistency of the scores of the two examiners in the Functional Movement Screen (FMS). Material and methods. The study was carried out on a group of 85 persons who practiced professional sports such as boxing, volleyball and football. The tests were performed using the Functional Movement Screen’s device and protocol. Functional Movement Screen (FMS) evaluation was performed twice by two independent therapists at 15 minute intervals. Intra-class correlation coefficient (ICC) was used to analyze the reliability of measurements. Results. The strength of absolute compliance of the two examiners’ scores in the individual Functional Movement Screen (FMS) tests was: Test 1 - ICC = 0.9; Test 2 - ICC = 0.92; Test 3 - ICC = 0.96; Test 4 - ICC = 1; Test 5 - ICC = 0.94; Test 6 - ICC = 1; Test 7 - ICC = 0.91. Conclusions. The level of consistency between the two examiners in the Functional Movement Screen (FMS) is high (ICC = 0.98).